A Systematic Literature Review The Impact of ERP and DSS on Organizational Performance: The Mediating Role of Decision-Making Quality - Julianto, Dimas Gibran Julianto; Hamdani, Hamdani; Achmad, Gusti Noorlitaria; Ramadhani, Herry; Arifin, Zainal (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
The adoption of Enterprise Resource Planning (ERP) and Decision Support Systems (DSS) is increasingly widespread to improve organizational performance, yet the underlying mechanisms remain fragmented. This study aims to conduct a Systematic Literature Review (SLR) to identify the impact of ERP and DSS on organizational performance, highlighting the mediating role of decision-making quality. A systematic search was performed on four sources (Scopus, Web of Science, Google Scholar, and ProQuest) for the 2021–2025 period. From 217 initial records, 34 empirical studies were analyzed using thematic synthesis. The results show that both ERP and DSS positively affect organizational performance, directly and through the enhancement of decision-making quality. Decision quality encompassing speed, accuracy, and information completeness – acts as a significant mediator. The mediation effect is determined by factors including top management support, organizational culture, data quality, and user competency. The findings emphasize that IT investments only yield superior performance when accompanied by strengthened decision-making capabilities